The synthesis and properties of organic-inorganic hybrid polyoxometalates hybridised with asymmetric perylenediimides - Walters, Kai (2022)
In recent years there has been a growing interest in producing sustainable and efficient catalysts. Within this area of research there has been a focus in harnessing solar energy to drive reactions. Polyoxometalates (POMs) have attracted substantial attention in the field of photocatalysis due to their vast structural diversity, inherent redox activity, and photochemical properties. Despite the promising chemical profile of POMs and their potential in photocatalysis, they have been limited by their absorption characteristics which lie almost exclusively within the UV range and show little to no absorption in the visible light region.